Sosialisasi Kuliah Praktik (KP) sebagai Persiapan Karier Mahasiswa Saintek di Era Digital - Syofiana Sari, Rica; Satria, Deni; Yanto, Widja; Danang, Satria (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
This community service aims to help students get to know the Practical Lecture (KP) of strategic planning prepared by the Head of Study Program and Deka for 1 (One). This document is a reference in the implementation of students in the community, including in the use of knowledge obtained during lectures, program implementation, and lecture activities in the community. The socialization of Practical Lectures (KP) is one of the strategic efforts in equipping students of the Faculty of Science and Technology (Saintek) to be ready to face the dynamics of the world of work in the digital era. This activity aims to provide a comprehensive understanding of the essence, benefits, and procedures for implementing KP, which are directly related to the demands of competencies in today's industrial and professional sectors. In this socialization, the importance of mastery of technology, practical work experience, and the ability to adapt to digital changes as provisions for the career world is also emphasized. Through presentations from speakers from academic and industrial environments, it is hoped that students will gain new insights related to various opportunities and challenges in the midst of digital transformation. The results of this activity show an increase in students' understanding of the important role of KP in supporting career development, as well as a growth in motivation to prepare themselves more optimally in entering the world of work.